INTERNALISASI NILAI-NILAI ASWAJA MELALUI PENGAJARAN ILMU TAUHID DI PESANTREN DARUL HUDA SUMBERMANJINGWETAN MALANG (KAJIAN ANALISIS DESKRIPTIF) - Ahmad Dahri; Mahmudi Mahmudi (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
Basically, the religious principle which is owned by people have main related to the background, both in family, social as well as education. One of the absolute things is the attitude of diversity that always growth and development concurrently by the modern era. There who has tolerant, even the opposite of it is intolerant, however also there who is casual attitude. On the context of life that become the orientation are togetherness and peacefulness. therefore on the pesantren tradition famous as al-ahl assunnah wa al-jamaah or ASWAJA. Certainly, it is not all pesantren have similar definition to define the ASWAJA. Partially, there are also those who tend more serious and rigid to respond the diversity of life. Pesantren is traditional education containing transformation and transfer knowledge of diversity, particularly ASWAJA. Through were had come some phenomenon like “cekak nala,” “sumbu pendek,” and so on, it is necessary to look again at how the ASWAJA values are manifested. So it is necessary, dedication to implement ASWAJA values, the writer implements dedication in manifesting the values of ASWAJA through tauhid learning at the Darul Huda Sumbermanjing Wetan Islamic boarding school.